Navigating a cloud services agreement : A Swedish perspective - Lars Perhard, Advokat (Journal of Telecommunications and the Digital Economy, 2019)
Cloud Sweden is a story about how a group of experienced IT-people from different sectors of the industry came together and discussed a relatively new phenomenon called the Cloud; or what is today labelled as Cloud computing. And they realised there was a tremendous momentum and potential prosperity connected to it. They also concluded that in order to support potential users and to promote Sweden as an IT-oriented country in the forefront of the development there was a need for information – organisations considering migrating their IT functions to the Cloud should at least be able to make an informed decision. There are significant advantages with this new technology, but also a number of pitfalls that any user should be aware of. There were for example critical security issues at hand before when the servers were placed within the four walls of the office and there still are critical security issues relating to the Cloud. However, the issues to solve are different. Cloud Sweden was founded and the different branches of the group have produced a number of documents published on its website. Cloud Sweden has apart from a number of members working actively in the steering and competence groups several thousand members from the industry in a Linkedin network. In this article you will find a sample of what the legal group of Cloud Sweden has produced – a primer of legal issues that a migrant shall pay attention to before the leap into the Cloud.